A. \(z = \dfrac{7}{6} - 4i\).
B. \(z = \dfrac{6}{7} + 4i\).
C. \(z = - \dfrac{7}{6} - 4i\).
D. \(z = - \dfrac{7}{6} + 4i\).
D
Đặt \(z = a + bi;\,\,\,\,a,b \in \mathbb{Z}\)
\(\begin{array}{l}|z| + z = 3 + 4i\\ \Rightarrow \sqrt {{a^2} + {b^2}} + a + bi = 3 + 4i\\\left\{ \begin{array}{l}\sqrt {{a^2} + {b^2}} + a = 3{\rm{ (1)}}\\b = 4{\rm{ (2)}}\end{array} \right.\end{array}\)
Thay (2) vào (1) ta được:
\(\begin{array}{l}\sqrt {{a^2} + {{16}^2}} + a = 3\\ \Leftrightarrow \sqrt {{a^2} + {{16}^2}} = 3 - a\\ \Leftrightarrow \left\{ \begin{array}{l}a \le 3\\6a = - 7\end{array} \right.\\ \Leftrightarrow \left\{ \begin{array}{l}a \le 3\\a = \dfrac{{ - 7}}{6}\end{array} \right.\\ \Leftrightarrow a = \dfrac{{ - 7}}{6}\\ \Rightarrow z = - \dfrac{7}{6} + 4i\end{array}\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247